A direct carbon fuel cell with a CuO–ZnO–SDC composite anode. Issue 55 (23rd May 2016) - Hao, Wenbin; Mi, Yongli
Abstract : A direct carbon fuel cell with a CuO–ZnO–SDC composite anode was demonstrated. The maximum power density was 130 mW cm −2 at 700 °C. The results indicate that CuO–ZnO can be used as a nickel-free anode material for direct carbon fuel cells. Abstract : A direct carbon fuel cell with a copper oxide–zinc oxide–Sm0.2 Ce0.8 O2− x (CuO–ZnO–SDC) composite anode was demonstrated. Nano-sized SDC and CuO–ZnO were synthesized by utilizing a co-precipitation process and a solid state reaction, respectively. As-prepared materials were characterized by various techniques, and then used to fabricate single cells by a co-press and co-sintering method. Finally, a button cell was tested with a mixture of carbon black and ternary (Li, Na, and K) eutectic carbonates as the anode fuel. The inert environment of the anode compartment was protected by pure N2 or a mixture of N2 & CO2 . A maximum power density of 130 mW cm −2 was achieved using the mixture of N2 & CO2 as the anode gas at 700 °C. The results indicate that CuO–ZnO can be used as a nickel-free anode material for direct carbon fuel cells. Also, the modified anode gas of a N2 & CO2 mixture can enhance the performance of direct carbon fuel cells with a CuO–ZnO–SDC composite anode.